Performance comparison of controllers for solar PV water pumping applications. (September 2015) - Yadav, Kamlesh; Sastry, O.S.; Wandhare, R.; Sheth, N.; Kumar, M.; Bora, B.; Singh, Rashmi; Renu,; Kumar, A.
Highlights: First time a direct comparison of VFD and SPCM pump controllers is presented. Experimental proof is provided for major drawbacks in VFD controllers. Dominance of SPCM in terms of power quality, efficiency and water output is established. SPCM provides 70% more water using same PV array, motor & pump and under similar head. Abstract: This paper presents a detailed comparison of two different electronic controllers used for driving Solar Photovoltaic water pumping systems in India. A recently developed Sine-wave Pump Controller with MPPT (SPCM) having two stage converter topology offered better performance throughout the operational range, over the most popular controllers using the Variable Frequency Drives (VFD). This paper presents an exhaustive study of SPCM and VFD based controllers in terms of their operational performance at 10 m, 18 m and 20 m head, in terms of quality of output power and quantity of the total water delivered when connected to the same motor-pump set under similar conditions. SPCM with best MPPT efficiency of 99.4%, lowest THD of less than 3% and pumped 30% to 70% more water for same heads. The overall system efficiency of SPCM based pump is 18% higher than VFD based pumping system for the head corresponding to duty point. The output power quality of SPCM is considerably high, with superior sine-wave (crest-factor 1.42 and 1.56 for voltage & current), ensures no voltage spikes even at 60 m of cable length. Thus, the paper establishes performance dominance of SPCM over the VFD based controller through the measurement on actual sample.